TiO2 films with oriented anatase {001} facets and their photoelectrochemical behavior as CdS nanoparticle sensitized photoanodes - Wang, X.; Liu, G.; Wang, L.; Pan, Jian; Lu, G.; Cheng, H. (2011)
TiO2 films with oriented anatase {001} facets directly grown on titanium foil substrate were prepared via a facile hydrothermal route. The average size of {001} facets is as small as ca. 130 nm, and its thickness is around 600 nm. The obtained TiO2 film as a photoanode shows efficient photoelectrochemical capability. Furthermore, after coating with CdS nanoparticles (NPs), the TiO2 film with oriented {001} facets exhibited much improved photoelectrochemical water splitting ability (photocurrent). A unique Z-scheme electron/hole transport mechanism is proposed to occur on the interface of highly active TiO2 {001} facets and CdS NPs.